1998
DOI: 10.1074/jbc.273.28.17469
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Type 1 and Type 8 Ca2+/Calmodulin-sensitive Adenylyl Cyclases by the Gs-coupled 5-Hydroxytryptamine Subtype 5-HT7AReceptor

Abstract: The neurotransmitter serotonin (5-hydroxytryptamine, 5-HT) plays an important regulatory role in developing and adult nervous systems. With the exception of the 5-HT 3 receptor, all of the cloned serotonin receptors belong to the G protein-coupled receptor superfamily. Subtypes 5-HT 6 and 5-HT 7 couple to stimulation of adenylyl cyclases through G s and display high affinities for antipsychotic and antidepressant drugs. In the brain, mRNA for 5-HT 6 is found at high levels in the hippocampus, striatum, and nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 56 publications
5
44
1
Order By: Relevance
“…The mechanism by which the 5-HT7 receptors activate ERK1/2 has not been completely elucidated. According to some authors, activation of ERK1/2 is likely to occur as a consequence of the increase in both cAMP and calcium following activation of Gscoupled 5-HT7Rs (Baker et al, 1998). Indeed, treatment with inhibitors of either calcium or adenylyl cyclase interferes with the 5-HT7R-mediated ERK activation (Guseva et al, 2014).…”
Section: Mechanismmentioning
confidence: 99%
“…The mechanism by which the 5-HT7 receptors activate ERK1/2 has not been completely elucidated. According to some authors, activation of ERK1/2 is likely to occur as a consequence of the increase in both cAMP and calcium following activation of Gscoupled 5-HT7Rs (Baker et al, 1998). Indeed, treatment with inhibitors of either calcium or adenylyl cyclase interferes with the 5-HT7R-mediated ERK activation (Guseva et al, 2014).…”
Section: Mechanismmentioning
confidence: 99%
“…Culture-It has been reported that 5-HT 7 receptors are positively coupled to adenylyl cyclases, and the activation of 5-HT 7 receptors can stimulate adenylyl cyclases by increasing intracellular Ca 2ϩ (47). To further explore the role of cAMP in neuronal excitotoxicity, we next tested the effect of a 5-HT 7 receptor agonist AS 19 (48,49) in cultured cortical neurons.…”
Section: -Ht 7 Receptor Activation Does Not Induce Cell Death In Neumentioning
confidence: 99%
“…The heptahelical 5-HTR 5 subtype is less characterized (21). 5-HTR 6 and 5-HTR 7 are linked to G s protein-mediated stimulation of adenylyl cyclase (22)(23)(24)(25)(26)(27)(28)(29).…”
Section: S Erotonin (5-hydroxytryptamine (5-ht))mentioning
confidence: 99%